Decentralization Politics in Southeast Asia: A Narrative Literature Review of Institutional, Political, and Economic Dimensions (2014–2024) - Dedy Pribadi Uang (International Journal Labs, 2025)
This study aims to analyze the development of decentralization politics in Southeast Asia during the 2014–2024 period using a Narrative Literature Review (NLR) approach. The study focuses on four representative countries: Indonesia, the Philippines, Thailand, and Malaysia, each of which has distinct characteristics in the implementation of political, institutional, and economic decentralization. This study uses the NLR method with a narrative synthesis framework approach to identify, select, and synthesize scientific articles from the Scopus, DOAJ, and Google Scholar databases. The study results show that decentralization politics in Southeast Asia experiences a strong differentiation between democratic decentralization models (Indonesia and the Philippines) and controlled or constrained decentralization models (Thailand and Malaysia). The findings also indicate that the success of decentralization is influenced by a combination of political stability, regional institutional capacity, and the effectiveness of fiscal transfers. This article makes a theoretical contribution to the literature on decentralization politics and provides new research directions for understanding the relationship between institutions, power, and political economy in Southeast Asia